Stocking densities and feeding strategies in shrimp and tilapia polyculture in tanks - Simão, Bruno Rodrigo; Brito, Luis Otavio; Maia, Alex Sandro Campos; Miranda, Laizy Cabral; Azevedo, Celicina Maria da Silveira Borges (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the performance of Pacific marine shrimp (Litopenaeus vannamei) and tilapia (Oreochromis niloticus), in a polyculture in tanks subjected to different stocking densities and feeding strategies, in comparison with monoculture. Two experiments were performed, at the same time, in a completely randomized design with three treatments and four replicates each. Treatments for experiment I were: monoculture with 10 shrimp per m² (10S:0T); polyculture with 10 shrimp and 0.5 tilapia per m² (10S:0.5T); and polyculture with 10 shrimp and 1 tilapia per m² (10S:1T). Shrimp was the main crop, and feed was provided based on shrimp biomass. Treatments for experiment II were: monoculture with 2 tilapia per m² (2T:0S); polyculture with 2 tilapia and 2.5 shrimp per m² (2T:2.5S); and polyculture with 2 tilapia and 5 shrimp per m² (2T:5S). Tilapia was the main crop, and feed was provided based on fish requirements. In the experiment I, tilapia introduction to shrimp culture resulted in lower shrimp growth and poor feed conversion rate. In experiment II, shrimp introduction to tilapia culture did not interfere with fish performance. Polyculture is more efficient with the combination of 2 tilapia and 2.5 or 5 shrimp per m² and feed based on fish requirements.